2015
DOI: 10.1248/bpb.b15-00129
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Decitabine on Invasion and Exosomal Expression of miR-200c and miR-141 in Oxaliplatin-Resistant Colorectal Cancer Cells

Abstract: The effects of decitabine (DAC), a DNA methyltransferase (DNMT) inhibitor, on metastasis and exosomal expression of microRNAs were examined in SW620/OxR cells, a human colorectal cancer (CRC) cell line (SW620) with acquired resistance to oxaliplatin. This cell line shows an invasive phenotype by epithelial-mesenchymal transition. Two CRC cell lines, SW480, derived from primary CRC, and SW620, derived from lymph node metastasis, which were obtained from the same patient, as well as SW620/OxR, were also used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 32 publications
(47 reference statements)
2
26
0
Order By: Relevance
“…A recent study, encompassing a panel of ovarian adenocarcinoma cell lines, has also shown the inhibitory action of miR-200c on TUBB3 expression, which also depends on the nuclear localization of an RNA-binding protein, HuR [56]. Another study revealed that decitabine treatmentdependent upregulation of miR-200c and miR-141 promotes epithelial-like characteristics in highly invasive oxaliplatinresistant colorectal cancer cells [57].…”
Section: Mir-200c and Chemotherapy Resistancementioning
confidence: 94%
“…A recent study, encompassing a panel of ovarian adenocarcinoma cell lines, has also shown the inhibitory action of miR-200c on TUBB3 expression, which also depends on the nuclear localization of an RNA-binding protein, HuR [56]. Another study revealed that decitabine treatmentdependent upregulation of miR-200c and miR-141 promotes epithelial-like characteristics in highly invasive oxaliplatinresistant colorectal cancer cells [57].…”
Section: Mir-200c and Chemotherapy Resistancementioning
confidence: 94%
“…12,21 In oxaliplatin-resistant SW620 cells, which display mesenchymal features, treatment with a demethylating agent resulted in the restoration of expression of miR-200c and miR-141 as well as the epithelial marker, E-cadherin. 35,36 However, as previously mentioned, the demethylating agents used are not specific to the promoter regions of the miR-200 family, and other genes may be activated with demethylation and contribute to the phenotypic changes. It is hypothesized that repression of miR-200c and miR-141 was a marker for chemotherapy resistance.…”
Section: Therapeutic Potential: Mir-200 Family Changing Colon Cancer mentioning
confidence: 99%
“…2, 3 In addition, recent evidence has indicated that miRNAs can function as oncogenes or tumor suppressors. 4, 5 Many miRNAs were found to be aberrantly expressed in colorectal cancer (CRC) with the downregulation of miR-601, miR-192, miR-345, miR-215, and miR-612, and the upregulation of miR-223, miR-18a, miR-155, miR-31, and miR-224, when compared with those found in normal colon mucosa. 6, 7, 8, 9 Given their involvement in the initiation, progression, and metastasis of human cancers, some of these miRNAs have become studies of great interest.…”
mentioning
confidence: 99%